Evaluasi Formulasi Teh Celup dari Kombinasi Kulit Jeruk Manis (Citrus sinensis L.) dan Buah Ara (Ficus carica L.) sebagai Antibakteri terhadap Staphylococcus aureus - Husni, M. Irgisyach Aqilla; Simat, Marcelina Oktavia Mayang Sari; Suhartomi, Suhartomi; Hendrianto, Hendrianto; Syarifah, Siti; Putri, Maulinda; Widyawati, Tri (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
The development of natural-based antibacterial agents is essential to reduce dependency on antibiotics and the risk of resistance. Sweet orange peel and fig fruit contain bioactive compounds with potential antibacterial effects. This study aimed to develop tea bag formulations made from sweet orange peel with the addition of fig fruit as an additive and to evaluate their in vitro antibacterial activity against Staphylococcus aureus. This experimental study employed two approaches, including disc diffusion and microdilution on several combination formulations of sweet orange peel and fig tea bags. The formulations consisted of F1 (1 g sweet orange peel and 1 g fig), F2 (1.5 g sweet orange peel and 0.5 g fig), and F3 (1.75 g sweet orange peel and 0.25 g fig). The disc diffusion assay showed that all formulations exhibited weak antibacterial activity against Staphylococcus aureus, producing inhibition zones of approximately 6–7 mm, except for F3 infusion, which demonstrated the widest inhibition zone with a mean diameter of about 8.21 mm (P-Value = 0.688). In the microdilution test, the MIC of F3 infusion was found to be 40 mg/mL, while the MBC was not detected at the tested concentrations. Overall, it can be concluded that the infusion of the tea bag formulation containing 1.75 g sweet orange peel and 0.25 g fig was the most promising combination; however, its antibacterial activity remained weak and was bacteriostatic rather than bactericidal.